Development of a family-based pulmonary rehabilitation programme: an exploratory study. (July 2015) - Marques, Alda; Gabriel, Raquel; Jácome, Cristina; Cruz, Joana; Brooks, Dina; Figueiredo, Daniela
Abstract Purpose: This study explored the expectations of patients with chronic obstructive pulmonary disease (COPD) and family members about a family-based pulmonary rehabilitation (PR) programme; developed and implemented a family-based PR programme and explored the impacts of the intervention on patients and family members. Method: Patients with COPD and family members were interviewed. A family-based PR programme was designed. Patients' breathlessness, muscle strength, exercise tolerance, functional balance and health-related quality of life were collected pre/post-programme. Family coping and adjustment to illness were measured in patients and family members. Focus groups were conducted after the programme. Results: Patients (n = 35; 69 ± 10 years; FEV1 62 ± 15% predicted) and family members (n = 35; 57 ± 12 years) had similar expectations/needs about a PR programme. Nine dyads participated. Patients' quadriceps strength, exercise tolerance and functional balance improved significantly (all p values < 0.023). Patients and family members seem to use more positive coping behaviours (p = 0.026; p = 0.011). Patients (n = 7; 78%) and family members (n = 8; 89%) considered having more knowledge about COPD and its management. Patients felt more functional (n = 9; 100%) and reported their family members to be more active (n = 3; 38%). In family members' perspective, their relationship with the care receiver was enhanced (n = 2; 22%). Conclusions: PR programmes, if inclusive of family members, may enhance the skills of the whole family to manage COPD. Implications for Rehabilitation Patients with chronic obstructive pulmonary disease (COPD) and their family members have similar expectations and needs about a family-based pulmonary rehabilitation (PR) programme. A family-based PR programme is feasible to implement within primary care. PR programmes, if inclusive of family members, may enhance the skills of the whole family to manage COPD.